SISTEM INFORMASI PENDAFTARAN SISWA PADA LEMBAGA KURSUS DAN PELATIHAN INTERNATIONAL COLLEGE PURWOKERTO BERBASIS WEBSITE - Carolina Ety Widjayanti; Priska Candra Sanubari; Dhany Faizal Racma; Antonius Ary Setyawan (Electro Luceat, 2023)
International College Purwokerto is a Foreign Language Course and Training Institute (LCT) and tutoring that provides additional learning services provided to students to increase the intensity of learning and increase proficiency in foreign languages. The registration system that now runs at LCT International College Purwokerto, has not been systemized in managing registration data, so reporting student enrollment requires time to work on the data of students who apply. Every semester, students where LCT is increasing so that student data has not been stored properly. Student data is still written in books, when within a certain period of time the student data is required to search for student documents so that it takes time to search. During this pandemic,LCT International College urgently needs facilities such as student registration through the website so that students can register online from their homes by filling in their personal data and files needed without having to come to LCT so that it is more time efficient. In addition to assisting the LCT in the registration of this inventory system using the prototype method in the system development stage. To collect the data, researchers conduct interviews, data documentation and observations. This system was built with the aim to help the student enrollment process at LKP International College to be more efficient. System design uses UML models such as usecase diagrams and, class diagrams, activity diagrams. The programming languages used are PHP and MySQL databases. The results of hypothesis testing and benefit tests can be found that the difference in the average time of the student registration process before and after using the system is 19,888 minutes (before using the system) and 9,320 minutes (after using the system). With benefit testing obtained with excellent results with aimed that usability of 93.33%, learnability of 73.33%, eficiency of 95.83.